2015
DOI: 10.1080/10632921.2015.1013169
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Perceptions of Stakeholders on Authentic Leadership in Strategic Planning in Nonprofit Arts Organizations

Abstract: Nonprofit arts organizations are experiencing declines not unlike those experienced by other nonprofits twenty years ago. At that time, key leadership in strategic planning reversed trends of decline. This research explores stakeholder perceptions of authentic leadership in strategic planning in nonprofit arts organizations in metropolitan Detroit. Eight arts organizations were represented in the study. Findings suggest that there is an insufficient application of authentic leadership traits, such as trust and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Así, se debe tener claro que la confianza en estas entidades es extremadamente frágil, puesto que es muy difícil conseguirla, pero muy fácil perderla. Consecuentemente, el principal desafío de una ESFL es obtener legitimidad de cara a todos aquellos que de una manera u otra se relacionan con ella, siendo por lo tanto clave la transparencia como elemento fundamental para garantizar dicha legitimidad (Herlin, 2015), así como confianza (Herman y Renz, 1999;Fisher, 2015), credibilidad social (Brown y Moore, 2001;Huang, 2017), honestidad (Rhine, 2015) y legalidad (Elechiguerra, Corral-Lage y Maguregui, 2015;Peng, Pandey y Pandey, 2015) para que éstas puedan desarrollarse y avanzar en el cumplimiento de su misión.…”
Section: La Transparencia En La Emisión De Información Externa En Lasunclassified
“…Así, se debe tener claro que la confianza en estas entidades es extremadamente frágil, puesto que es muy difícil conseguirla, pero muy fácil perderla. Consecuentemente, el principal desafío de una ESFL es obtener legitimidad de cara a todos aquellos que de una manera u otra se relacionan con ella, siendo por lo tanto clave la transparencia como elemento fundamental para garantizar dicha legitimidad (Herlin, 2015), así como confianza (Herman y Renz, 1999;Fisher, 2015), credibilidad social (Brown y Moore, 2001;Huang, 2017), honestidad (Rhine, 2015) y legalidad (Elechiguerra, Corral-Lage y Maguregui, 2015;Peng, Pandey y Pandey, 2015) para que éstas puedan desarrollarse y avanzar en el cumplimiento de su misión.…”
Section: La Transparencia En La Emisión De Información Externa En Lasunclassified
“…The review performed by them indicated the publication, between 2014 and 2016, of only eight articles in which an exclusively qualitative approach was adopted. The studies aimed at: investigating AL in school environments (Glowacki-Dudka & Griswold, 2016;Greenier & Whitehead, 2016;Shapira-Lishchinsky & Levy-Gazenfrantz, 2015); analyzing gender issues and AL (Liu, Cutcher, & Grant, 2015); proposing AL for specific environments such as strategic planning (Rhine, 2015); analyzing paradoxes of authenticity in the practice of leadership (Nyberg & Sveningsson, 2014); and analyzing AL in nursing practices (Shapira-Lishchinsky, 2014; Waite, McKinney, Smith-Glasgow, & Meloy, 2014). None of the studies, therefore, investigated the congruence between the leader's discourse and the AL theory, aiming to enlarge it and/or contribute to its consolidation.…”
Section: Liderazgo Auténtico: Un Análisis Temático Teórico Del Discurmentioning
confidence: 99%
“…This identity may be perceived as a key component when maintaining the continued support of stakeholders (Young, 2001). More specific to fine arts nonprofits, Rhine (2015) suggested that "professional leadership of nonprofit fine and performing arts organizations faces a longterm need to plan strategically to deal with changes in the national landscape of arts patronage, such as decreasing attendance and shrinking public and private financial support" (p. 3). Rhine (2015) examined "stakeholder perceptions of interactions between authentic leadership traits and strategic planning in nonprofit arts organizations" (p. 4).…”
Section: Teacher Leadershipmentioning
confidence: 99%
“…Respondents described leadership of the strategic planning process as either effective, moderately effective, or ineffective (Rhine, 2015, p. 8). Additionally, respondents perceived authentic leaders as having aligned the values of the organization with their own (Rhine, 2015). Rhine (2015) suggested that there was a distinct connection between "authentic leadership traits and satisfaction with the organization.…”
Section: Teacher Leadershipmentioning
confidence: 99%
See 1 more Smart Citation